PENGEMBANGAN E-LKPD BERBASIS CROSSWORD PUZZLE PADA MATERI KENAMPAKAN ALAM DI PERMUKAAN BUMI UNTUK MENINGKATKAN SELLF CONFIDENCE SISWA KELAS V SD NEGERI 1 WAJAK KABUPATEN MALANG - S, Ribkah Katherina; Ragil Tri Oktaviani; Khoirul Wafa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this research is to develop Crossword Puzzle-based E-LKPD on the material of natural appearances on the Earth's surface as a form of increasing Self Confidence of fifth grade students at SD Negeri 1 Wajak Malang Regency. The research method uses Research and Development (R&D) with the ADDIE model development phase: analysis, design, development, implementation, and evaluation. Information data collection through observation, interviews, questionnaire sheets, and documentation. It is known that the results of the product validity of material experts reached a value (98%), media (98%), and language (90%) categorized as